#SB40 Side event: Planning climate adaptation in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
National adaptation plans (NAPs) provide an important means for countries to define strategic responses to climate change over the medium- to long-term, for food security, livelihood, and development purposes. Agriculture is especially important component of NAPs for developing countries, as it is a significant contributor to GDP and employment. This side event during #sb40 featured the release of the CCAFS policy brief No. 9 “Climate adaptation and agriculture: Solutions to successful national adaptation plans,† and a panel discussion of research, policy and finance needs as countries implement national adaptation planning (NAP) processes. Photos: V. Atakos (CCAFS)